Penguatan Kompetensi Guide: Studi Pengalaman Pelatihan Mahasiswa di Museum Perkebunan Indonesia 1 Medan - Andina, Syahna Wulan Andina; Wandini, Putri; Harahap, Artika Hazra; Dongoran, Mustopa; Rahmatain, Imam Baihaqi; Kurniawan, Angge; Windari, Sri (Dampeng: Journal of Art, Heritage and Culture, 2025)
This study aims to analyze the design and implementation of guide training at the Museum Perkebunan Indonesia I (Musperin I) in Medan and to examine students’ experiences in strengthening their competencies as prospective museum guides. This research employs a qualitative descriptive approach using a case study method. Data were collected through field observations, in-depth interviews with student trainees and instructors, and documentation of training activities. The findings indicate that the guide training program at Musperin I is designed based on a competency-based approach, emphasizing a balance between mastery of plantation history knowledge, communication and interpretation skills, visitor management, and professional ethics. The training experience has a positive impact on improving students’ understanding of local history, storytelling abilities, self-confidence, and professional readiness in guiding museum visitors. Furthermore, the training highlights the role of museums as effective contextual learning spaces that integrate theoretical knowledge with practical guiding experience. Therefore, the guide training program at Musperin I contributes to the development of competent, professional, and adaptive museum guides who are responsive to visitor needs and the dynamics of contemporary museology, while also reinforcing the museum’s role as an educational institution and a center for cultural heritage preservation. [Penelitian ini bertujuan untuk menganalisis desain dan pelaksanaan pelatihan guide di Museum Perkebunan Indonesia I (Musperin I) Medan serta mengkaji pengalaman mahasiswa dalam memperkuat kompetensi sebagai calon pemandu museum. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan metode studi kasus. Data dikumpulkan melalui observasi lapangan, wawancara mendalam dengan mahasiswa peserta pelatihan dan instruktur, serta dokumentasi kegiatan pelatihan. Hasil penelitian menunjukkan bahwa pelatihan guide di Musperin I dirancang berbasis kompetensi dengan menekankan keseimbangan antara penguasaan pengetahuan sejarah perkebunan, keterampilan komunikasi dan interpretasi, manajemen kunjungan, serta etika profesi pemandu. Pengalaman pelatihan memberikan dampak positif terhadap peningkatan pemahaman sejarah lokal, kemampuan storytelling, kepercayaan diri, serta kesiapan profesional mahasiswa dalam memandu pengunjung museum. Pelatihan ini juga memperlihatkan peran museum sebagai ruang pembelajaran kontekstual yang efektif dalam mengintegrasikan teori dan praktik kepemanduan. Dengan demikian, pelatihan guide di Musperin I berkontribusi dalam membentuk pemandu museum yang kompeten, profesional, dan adaptif terhadap kebutuhan pengunjung serta perkembangan museologi kontemporer, sekaligus memperkuat fungsi museum sebagai institusi edukasi dan pelestarian warisan budaya.]